The Effect of Ease of Transaction, Promotion and Utilization of Shopeepay on the Decision to Use Digital Money on STIE Wibawa Karta Raharja Students - Duki Adam; Frisca Wulan Febriyanti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
It may be concluded that a selection is a way or choice from numerous alternatives, in accordance with high quality hobbies by way of the use of identifying an opportunity this is considered the maximum worthwhile. This research is a part of survey studies, the survey method is used to obtain information from certain places that describe a variable and real events and what they're, with the aid of dispensing questionnaires to STIE Wibawa Karta Raharja students.This studies turned into assisted by means of the use of the SmartPLS statistical device. Based on the outcomes of this study, the authors finish as follows, the transaction comfort variable has a fantastic and large effect on the selection to use digital cash for STIE Wibawa Karta Raharja college college students.Promotion variables have a high-quality and massive impact on picks to use virtual money for STIE Wibawa Karta Raharja college students.Shopeepay usage variable has a excellent and substantial effect on choices to apply digital cash for STIE Wibawa Karta Raharja college students.Between the variables of ease of transactions, promoting and usage of Shopeepay have a fantastic and huge impact concurrently on the selection to apply digital coins for STIE Wibawa Karta Raharja college students by using way of having a medium model, meaning that the model is right sufficient to provide an explanation for usage choices.